2021
DOI: 10.3390/ma14216476
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance and Failure Mode of Mandibular Molar Restored by Occlusal Veneer: Effect of Material Type and Dental Bonding Surface

Abstract: This study assesses the effect of the material type (lithium disilicate, zirconia, and polymer-infiltrated ceramic) and dental bonding substrates (dentin, dentin with intra-coronal cavity, and dentin with composite filling) on the fracture resistance and failure mode of molars restored by occlusal veneers. Methods: Ninety occlusal veneers, fabricated from either lithium disilicate, zirconia, or polymer-infiltrated ceramic, were adhesively bonded to teeth prepared with either dentin, dentin with intra-coronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…They proposed that the recent study's higher fracture strength in dentin could be due to the improvement of a newly developed so‐called universal bonding system. On the other hand, the study by Walid Al‐Zordk et al ( 2021 ) has shown that the fracture resistance within veneers bonded to dentin, dentin with intra‐coronal cavity, and dentin with the composite filling was not significantly different. However, their fracture resistance is above human regular masticatory forces in molars.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They proposed that the recent study's higher fracture strength in dentin could be due to the improvement of a newly developed so‐called universal bonding system. On the other hand, the study by Walid Al‐Zordk et al ( 2021 ) has shown that the fracture resistance within veneers bonded to dentin, dentin with intra‐coronal cavity, and dentin with the composite filling was not significantly different. However, their fracture resistance is above human regular masticatory forces in molars.…”
Section: Discussionmentioning
confidence: 91%
“…However, their fracture resistance is above human regular masticatory forces in molars. Also, by varying dental bonding surfaces, different overlays' materials have to be considered (Al‐Zordk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the adhesion of resin cements to zirconia is still questionable due to its chemically inert surface and lack of micro-mechanical interlocking [ 7 ]. A resin-bonded fixed dental prosthesis made from zirconia exhibits more adhesive failure than that made from lithium disilicate [ 8 , 9 ]. Appropriate resin bonding protocols are crucial for the clinical success of zirconia restorations.…”
Section: Introductionmentioning
confidence: 99%
“…They have high quantity of glass in their structure, which makes them among the most naturallooking materials [22] . The proven competence of lithium disilicate material has been acknowledged which encourages its use in restoring worn teeth through a more conservative approach [4] . These days, the CAD/CAM hybrid ceramics have been presented with rapid restoration manufacturing with no need for firing after milling and uncomplicated intraoral mending of the restoration using direct composite material [22] .…”
Section: Introductionmentioning
confidence: 99%